Perdoem a Falta de Escolha, os Dias Eram Assim - Almeida, Vanessa de (Trabalhos de Antropologia e Etnologia, 2020)
Going underground took place in the context of a dictatorial regime. Having the so-called “mergulho” as a starting point, we proposed analyze of the modes of transmission of that particular experience both within the political organization and also in the family milieu. The key objective is to understand the process of memory transmission and how it is apprehended by the second generation, taking into account Michael Pollock’s idea of memories that are almost inherit.